The lesson (phonetic and morphological) with Al-Jahiz (who died in 522 AH) (Journal of the College of Basic Education, 2023)
Amr bin Bahr, who died in the year 255 A.H. (Al-Jahiz), was a brilliant writer and linguist.He wrote on most of the sciences, especially language sciences, its pronunciation, rhetoric, style, and structures.about fundamental and logical sciences, human, animal and plant sciences, so write down his book (The Statementand al-Tabyeen), and his book (The Animal) on the characteristics of animals and the nature of their life, and a thousand on the nature of human beings.And the behavior of people and their moral and moral qualities, so without you (the miserly one) and (the leprous, the blind, and the limp)and Al-Holan) are witnesses to this